ÓLEO VOLÁTIL DE CUNILA MICROCEPHALA: COMPOSIÇÃO QUÍMICA, FRACIONAMENTO E ATIVIDADE CITOTÓXICA - LOURO, G. M.; SIMIONATTO, E.; NICOLAU, C. L.; SILVA, J. C. M.; COSTA, E. R; SILVA, V. S. (ANAIS DO ENIC, 2016)
-